A Review of the Inhibition of the Mitochondrial ATP Synthase by IF1 in vivo: Reprogramming Energy Metabolism and Inducing Mitohormesis - García-Aguilar, Ana; Cuezva, José M. (Frontiers in Physiology, 2018)
The ATPase Inhibitory Factor 1 (IF1) is the physiological inhibitor of the mitochondrial ATP synthase. Herein, we summarize the regulation of the expression and activity of IF1 as a main driver of the activity of oxidative phosphorylation (OXPHOS) in mammalian tissues. We emphasize that the expression of IF1, which is a mitochondrial protein with very short half-life, is tissue-specifically expressed and primarily controlled at posttranscriptional levels. Inhibition of the activity of IF1 as inhibitor of the ATP synthase under normal physiological conditions is exerted by phosphorylation of S39 by a cAMP-dependent PKA-like activity of mitochondria in response to different physiological cues. Conditional tissue-specific transgenic mice overexpressing IF1 in colon, or a mutant active version of IF1 (IF1-H49K) in liver or in neurons, revealed the inhibition of the ATP synthase and the reprograming of energy metabolism to an enhanced glycolysis. In the IF1-H49K models, the assembly/activity of complex IV and the superassembly of complex V are also affected. Moreover, the IF1-mediated inhibition of the ATP synthase generates a reactive oxygen species (mtROS) signal that switches on the expression of nuclear genes that facilitate adaptation to a restrained OXPHOS. In contrast to normal mice, metabolically preconditioned animals are partially protected from the action of cytotoxic agents by upgrading the activation of stress kinases and transcription factors involved in resolving metabolic adaptation, the antioxidant response, cell survival, and the immune response of the tissue microenvironment. Altogether, we stress a fundamental physiological function for the ATP synthase and its inhibitor in mitohormesis.